Erratum to: Genetic markers for urine haptoglobin is associated with decline in renal function in type 2 diabetes in East Asians (Scientific Reports, (2018), 8, 1, (5109), 10.1038/s41598-018-23407-1) - Gurung R.L. (Nature Publishing Group, 2019)
10.1038/s41598-018-31990-6